Interface modification method for PPTA-enhanced carboxyl PC damping film embedded thermoplastic composite material
By surface modification of PPTA fibers and polycarbonate, and molecular bridges are built between the interfaces of fibers, resins and rubber to form chemical bond connections, the existing large-dampened aramid fiber reinforced thermoplastic composite materials have been solved. The weak problem significantly improves the overall performance of the material.
Patent Information
- Application Number
- CN202411560431.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
AI Technical Summary
The interface bonding performance of existing large-dampening aramid fiber reinforced thermoplastic composite materials is weak, which affects its application in engineering fields such as high strength and impact resistance.
By surface modification of PPTA fibers and polycarbonate, the PPTA surface is etched with CaCl2 ethanol solution to increase the surface chemical reactive sites and roughness, and build it between the interfaces of fiber, resin and rubber materials. The molecular bridge forms chemical bond connection through KH560 as an intermediate graft.
The interface bonding performance and overall performance of the thermoplastic composite materials embedded in PPTA-enhanced carboxyPC damping film are significantly improved, with the H extraction force being increased by 137% and the interlayer shear stress being increased by 74%.
Smart Images

Figure CN119431841A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a technical research field of interface modification of high damping fiber reinforced thermoplastic composite materials, and in particular to an interface modification method of a PPTA reinforced carboxyl PC damping film sandwiched thermoplastic composite material. Background Art
[0002] Compared with thermosetting composite materials, high-damping thermoplastic composite materials have the advantages of high strength, recyclability, environmental protection, good flexibility and shrinkage resistance, etc., and are the inevitable trend of the future development of composite materials.
[0003] Embedded damping film aramid fiber reinforced polycarbonate composite laminate is a three-phase damping composite material, in which the matrix phase polycarbonate (PC) is a thermoplastic resin with high strength, high toughness, oxidation resistance and flame retardancy, and can be melted and reused; the reinforcing phase is para-aramid fiber (PPTA), which has excellent impact resistance and fatigue resistance; the functional phase is methyl vinyl silicone rubber (VSI), which is sandwiched in the fiber resin prepreg layer as a damping film, and through the co-grafting process, it is made into a thermoplastic damping composite material with functions such as high temperature resistance, vibration reduction and noise reduction. This composite material integrates light weight and large damping functions, and has broad application prospects in aerospace, bulletproof and other fields.
[0004] However, the curing process of thermoplastic resin is only a change in the state of matter, and basically no chemical changes occur, resulting in weak adhesion between resin and fiber. In addition, PPTA has a smooth surface, lacks polar groups, and has good thermal and chemical stability, which makes the interface between PPTA and reinforced thermoplastic composites very easy to loosen, seriously affecting its application in high-strength, impact-resistant and other engineering fields. At present, there are few research reports on aramid fiber reinforced thermoplastic composites embedded with damping films. Therefore, improving the interface bonding performance of high-damping aramid fiber reinforced thermoplastic composites has always been a difficulty and focus of scholars.
[0005] Chinese patent application CN 115449097 A discloses a method for surface modification of aramid nanofibers to enhance the interfacial adhesion of rubber composite materials. Tannic acid (TA) and polyethyleneimine (PEI) are polymerized in an alkaline solution to form a TA / PEI (TP) thin layer, which is deposited on the surface of aramid fiber (AF) to introduce functional groups such as hydroxyl and amino groups. A nanostructure is constructed on the surface of AF using an aramid nanofiber (ANF) coating to improve the interfacial adhesion between the fiber and rubber. The research contribution is to improve the interfacial adhesion between the fiber and rubber by constructing a nanostructure on the surface of the aramid fiber. The rubber material is not involved. The surface nanostructure is only constructed on the aramid fiber to improve its surface adhesion, thereby enhancing the interfacial bonding performance between the fiber and the rubber.
[0006] Chinese patent application CN 109610171 A discloses a method for increasing the surface roughness of aramid fibers. The aramid fibers are directly irradiated with ultraviolet light, and the modified silica is grafted onto the surface of the aramid fibers with the help of the bridging effect of polyacrylic acid, thereby obtaining aramid fibers with roughened surfaces. This patent application utilizes the fact that SiO2 particles have a large surface area and a high surface energy, which results in poor compatibility between highly hydrophilic SiO2 and highly hydrophobic rubber matrix, and is prone to agglomeration; aramid fiber AF has a distinct skin-core structure and an extremely smooth surface, which results in poor interfacial bonding between AF and the polymer matrix. This phenomenon limits the application of aramid fibers in rubber. The purpose of this patent application is to provide a method for preparing surface-roughened aramid fibers, which can not only overcome the agglomeration of SiO2, but also regulate the surface roughness of aramid fibers. It achieves close bonding between the aramid fiber and the matrix by increasing the surface roughness of the aramid fiber and improving the interfacial friction between the aramid fiber and the matrix. However, it does not involve how the rough aramid fiber with a rough surface achieves improved interfacial bonding with the matrix or rubber through chemical changes. Therefore, the degree of improvement in the interfacial bonding between the aramid fiber and the polymer matrix is limited by the interfacial physical friction coefficient if it only increases the interfacial contact area and the interfacial physical friction.
[0007] Zhao Zhiping, Gong Xiangjun, et al., Application of modified aramid fiber in the preparation of high-performance rubber composites, Journal of Ludong University (Natural Science Edition), 2023, 39(3): 264-272, introduced a variety of methods to enhance the adhesion between aramid and rubber, including physical modification and chemical modification. Chemical modification is based on the structure of aramid fiber, using chemical reagents to etch the surface, destroy crystalline substances, or graft reaction on the group, etc.; physical modification is to produce grooves or free radical reaction active centers on the surface of aramid fiber, thereby introducing a variety of polar groups, changing the fiber surface structure and morphology, and thus improving the roughness and wettability of aramid fiber.
[0008] This paper studies the enhancement of aramid adhesion to rubber, and reviews the application of modified aramid fiber reinforced rubber composites in sealing rubber, impact-resistant rubber, rubber damping materials, etc. The paper starts from the structure of aramid fiber and uses chemical and physical methods to enhance the adhesion between aramid and rubber. It does not involve rubber materials or that type of rubber material. It all belongs to the method of improving the interface bonding performance between the modified fiber and the matrix or rubber by changing the physical properties of the aramid fiber surface. It does not involve the chemical changes of the fiber-matrix interface. The same method is used to improve the interface bonding strength between aramid fiber and polymer matrix, and the degree of improvement is also limited by the interface physical friction coefficient.
[0009] Dong Chaoliang, Wang Yaoxian, et al., Study on the interfacial bonding properties of aramid fiber reinforced resin matrix composites, Engineering Plastics Applications, Vol. 40, No. 3, March 2012.
[0010] In order to improve the interfacial bonding properties of aramid fiber reinforced resin-based composites, this paper starts with the resin matrix, synthesizes a new thermosetting resin (AFR-T) as the matrix of aramid composites based on the similar compatibility principle and the structural characteristics of aramid, uses untreated aramid as reinforcement, and prepares AFR-T / aramid fiber composites by hot pressing. The new resin used here is thermosetting, and the aramid fiber used is untreated fiber. The goal of the study is to explore the wettability and interfacial bonding properties between AFR-T resin and aramid fiber. The molecular structures are similar and can be integrated with each other to improve the interfacial bonding properties. This paper is only a physical change - improving the interfacial bonding properties of the fiber and the resin matrix based on the similar compatibility principle of molecular structure. The same method is used to improve the combined force of the interface between the aramid fiber and the polymer matrix, and the degree of improvement is also limited by the physical friction coefficient of the interface.
[0011] To sum up: the above-mentioned studies are all aimed at the fact that the surface of aramid fiber is smooth and the chemical reaction activity is poor, resulting in weak interfacial adhesion between it and the resin or rubber matrix, thereby affecting the overall mechanical properties of the composite materials of aramid fiber and resin matrix or rubber matrix. The purpose is to improve the interfacial bonding performance between the modified fiber and the resin matrix or rubber by changing the physical properties of the aramid fiber surface or synthesizing a new thermosetting resin, such as increasing the surface roughness value of aramid fiber, adding nanostructures to the surface of aramid fiber, improving the surface adhesion of aramid fiber, and improving the interfacial fusion performance between fiber and synthetic resin through the principle of molecular structure similarity and compatibility. None of them involve the chemical changes at the interface between fiber and matrix, nor the molecular structure and molecular bond connection of the interface material, resulting in low interlayer bonding performance and the need to improve the overall mechanical properties. The present application is to modify the surface of aramid fiber, thermoplastic resin and damping material, and to cause chemical co-grafting under the action of silane coupling agent KH560 so that chemical bonds are formed between the interfaces of the two phases of the three-phase composite material, and to connect the three phases of different materials into a whole by molecular bridges, thereby improving the mechanical properties of the overall structural interface at the molecular chemical bond level, and to achieve molecular bridge connection between the interfaces of aramid fiber, thermoplastic resin and damping material through co-grafting of chemical changes. Summary of the invention
[0012] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a PPTA-reinforced carboxyl PC damping film sandwich thermoplastic composite interface modification method, which can improve the interface bonding performance of the three-phase composite material of para-aramid fiber, polycarbonate and methyl vinyl silicone rubber, so that it can be widely used.
[0013] To achieve the above object, the present invention adopts the following technical solutions:
[0014] A method for modifying the interface of an aramid fiber reinforced carboxyl polycarbonate damping film sandwiched thermoplastic composite material comprises the following steps:
[0015] 1) Carboxylation treatment is performed on the surface of a polycarbonate (PC) thermoplastic resin sheet, and the sheet is sealed and stored for later use;
[0016] 2) Cut methyl vinyl silicone rubber (VSI) into particles and put them into a beaker. Add dichloromethane solvent to the beaker at a mass ratio of 4:1 to dissolve the granular VSI into liquid. Seal and store for later use.
[0017] 3) Cut the para-aramid fiber (PPTA) woven fabric into multiple samples, put them into an ultrasonic cleaning machine for ultrasonic cleaning, and take them out to dry;
[0018] 4) Prepare a 10% CaCl2 ethanol solution, place the clean and dry PPTA sample into the prepared CaCl2 ethanol solution, and place it in a high and low temperature alternating wet heat environment box at a constant temperature of 60°C for 2 hours;
[0019] 5) Take out the PPTA sample treated in step 4), clean the PPTA sample with deionized water and dry it, then prepare KH560 ethanol solution and add deionized water to promote hydrolysis, and evenly apply it to the surface of the PPTA sample;
[0020] 6) applying the VSI liquid in step 2) to the surface of a PPTA sample treated in step 5) and drying it to make a damping film, and applying a layer of the prepared KH560 ethanol solution on the damping film;
[0021] 7) The PC thermoplastic resin sheets processed in step 1) and the PPTA samples processed in step 5) are alternately stacked and laid to form a matrix phase and a reinforcement phase combination, and the damping film prepared in step 6) is sandwiched as a functional phase into the center position of the aforementioned matrix phase and reinforcement phase combination according to the designed layering sequence to form a composite material preform, and the laminated composite material preform is placed in a press molding die, and after hot-pressing co-grafting molding through a co-grafting process curve, pressurization is applied to eliminate residual stress to obtain a PPTA / PC laminated workpiece embedded with a damping film.
[0022] As a further technical solution, the carboxylation treatment in step 1) uses a dichloromethane solution and a 1 mol / L hydrochloric acid solution.
[0023] As a further technical solution, the particle size of the methyl vinyl silicone rubber in step 2) is 3×3×3 cubic millimeters.
[0024] As a further technical solution, the cleaning time in step 3) is 20 minutes.
[0025] As a further technical solution, the mass fraction of the CaCl2 ethanol solution in step 4) is 10%.
[0026] As a further technical solution, the mass fraction of the KH560 ethanol solution in step 5) is 7%, and the volume of deionized water is 5 ml.
[0027] As a further technical solution, the thickness of the damping film in step 6) is 0.1-0.5 mm.
[0028] As a further technical solution, the mass fraction of the KH560 ethanol solution in step 6) is 7%.
[0029] As a further technical solution, the working pressure per unit area of the press molding die in step 7) is 1 MPa.
[0030] The working principle of the present invention is as follows:
[0031] Aramid fiber reinforced thermoplastic resin-based composite materials have excellent bulletproof and impact resistance. In order to improve the interfacial bonding performance of para-aramid fiber (PPTA) reinforced polycarbonate (PC) composite laminates embedded with methyl vinyl silicone rubber (VSI) damping film, PPTA was surface etched with CaCl2 ethanol solution to increase its surface chemical reaction active sites and surface roughness values. Then γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) was used as an intermediate grafting agent to build molecular bridges between the interfaces of fiber, resin and rubber materials to form chemical bonds, so that the three materials are combined into a whole between the two phases at the interface.
[0032] Polycarbonate (PC) is an important thermoplastic engineering resin with good mechanical properties, high temperature stability and impact resistance. However, due to the lack of polar functional groups in the molecular chain, the bonding performance with other materials is poor, so it is not widely used in composite materials. To solve this problem, polar groups need to be introduced on its surface to change its chemical inertness. Its main chain carries an ester group (-COOCH3). When hydrolyzed with dichloromethane and hydrochloric acid solution, the ester group will be hydrolyzed into a carboxyl group (-COOH). This reaction introduces a carboxyl functional group on the PC surface, thereby improving its surface activity. The specific process is: first, a layer of dichloromethane solution is brushed on the surface of a clean and dry PC sheet to dissolve the PC surface, and then fully infiltrated with 1 mol / L hydrochloric acid solution, and placed in a beaker and sealed. The sealed beaker is placed in a high and low temperature alternating wet and hot environment box with a working temperature of 60°C for hydrolysis treatment for 2 hours to obtain surface carboxylated polycarbonate.
[0033] PPTA is a high-performance synthetic fiber with excellent mechanical properties and chemical stability. In order to further improve its performance, PPTA needs to be physically and chemically modified on the surface. Common surface modification methods include surfactant treatment, plasma treatment, chemical coating, surface modification, etc., which use chemical reactions or physical methods to introduce new functional groups on the PPTA surface or change the surface morphology to improve its performance.
[0034] Here, CaCl2 is used to treat the surface of PPTA in liquid phase. CaCl2 etches grooves on the surface of PPTA, increasing the attachment sites of resin and damping material. CaCl2 has ionic dipole effect with the amide bond in PPTA, and the -NH- in the amide group is exposed to get rid of hydrogen bond through complex reaction, so that its reactivity with the epoxy group in KH560 is increased. The clean and dry PPTA woven cloth is placed in an ultrasonic treatment container containing CaCl2 solution for 4 hours; an appropriate amount of KH560 ethanol solution is prepared, 5 ml of deionized water is added and allowed to stand for 30 minutes to promote its hydrolysis, and then the PPTA treated with CaCl2 is fully immersed in the modification solution and allowed to stand for 5 minutes to obtain modified PPTA.
[0035] Cut methyl vinyl silicone rubber (VSI) into particles and put them into a beaker. Then put VSI into dichloromethane solvent, the granular VSI will dissolve into liquid. Then brush the VSI liquid onto the surface of a treated PPTA sample and dry it to make a damping film. Then brush a layer of prepared KH560 ethanol solution on the damping film.
[0036] After modification, according to the designed layering sequence and the co-grafting process curve, the PPTA reinforced carboxyl polycarbonate damping membrane sandwich thermoplastic composite specimen can be prepared.
[0037] Beneficial Effects of the Invention
[0038] By modifying the interfacial bonding properties of the three-phase composite material of PPTA, polycarbonate and methyl vinyl silicone rubber, the interfacial bonding properties and overall performance of the PPTA-reinforced carboxyl polycarbonate damping film sandwich thermoplastic composite material are greatly improved. The experimental data show that the H extraction force of the specimen grafted with KH560 is increased by 137%, and the interlaminar shear stress is increased by 74%. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Shown is a diagram of the co-grafting process of three-phase materials;
[0040] Figure 2 Shown is the microscopic mechanism of KH560 grafted with PC and VSI;
[0041] Figure 3 Shown is the microscopic mechanism of KH560 grafted with PPTA and PC;
[0042] Figure 4 Shown is the microscopic mechanism of KH560 grafted with PPTA and VSI;
[0043] Figure 5 Shown is the co-grafting process;
[0044] Figure 6(a) shows the infrared spectrum of untreated PPTA;
[0045] Figure 6(b) shows the PPTA infrared spectrum of brush-coated KH560;
[0046] Figure 6(c) shows the infrared spectra of PC hydrolysis and PC grafted with KH560 after hydrolysis (the upper curve is KH560 grafted after hydrolysis, and the lower curve is PC after hydrolysis);
[0047] Figure 6(d) shows the infrared spectrum of VSI;
[0048] Figure 6(e) shows the infrared spectrum of VSI grafted KH560;
[0049] Figure 7 Shown is the SEM image of the microstructure of untreated PPTA;
[0050] Figure 8 Shown is the SEM image of the microstructure of PPTA treated with CaCl2 etching;
[0051] Fig. 9 Shown is the SEM image of the microstructure of PPTA grafted with KH560;
[0052] Fig.10 Shown is the SEM image of the untreated PC microstructure;
[0053] Fig.11 Shown is the SEM image of PC microstructure grafted with KH560 after hydrolysis;
[0054] Fig.12 Shown are the test locations indicated in the SEM images;
[0055] Fig.13 Shown are the test locations indicated in the SEM images;
[0056] Fig.14 Shown are the test locations indicated in the SEM images;
[0057] Fig.15 Shown is the EDS spectrum of the untreated PPTA surface;
[0058] Fig.16 Shown is the EDS spectrum of the KH560-PPTA interface;
[0059] Fig.17 Shown is the EDS spectrum of the KH560-PPTA-VSI interface;
[0060] Fig.18 The H test extraction process is shown;
[0061] Fig.19 Shown is the interlaminar shear test procedure. DETAILED DESCRIPTION
[0062] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0063] The structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no substantial technical significance. Any modification of the structure, change of the proportion relationship or adjustment of the size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention. At the same time, the terms such as "upper", "lower", "left", "right", "middle" and "one" quoted in this specification are only for the convenience of description, and are not used to limit the scope of the implementation of the present invention. The change or adjustment of their relative relationship should also be regarded as the scope of the implementation of the present invention without substantially changing the technical contents.
[0064] The present embodiment provides a method for modifying the interface of a PPTA-enhanced carboxyl-PC damping film-embedded thermoplastic composite material, wherein the surface of PPTA is treated with a CaCl2 ethanol solution to increase its surface roughness value and chemical activity; the surface of the PC sheet is treated with a dichloromethane and hydrochloric acid solution to hydrolyze the molecular structure of the PC surface under acidic conditions to introduce carboxyl groups; VSI is dissolved in dichloromethane to make a damping slurry, and then the VSI liquid is brushed onto the surface of a treated PPTA sample and dried to make a damping film; at this time, the three modified materials can be chemically co-grafted under the action of KH560 to form chemical bonds between the interfaces of the composite materials, and connected into a whole through molecular bridges, thereby achieving the purpose of improving the interface performance of the composite material. The prepared composite material samples are characterized by FTIR, SEM, EDS, H extraction test, and interlaminar shear test to verify the effectiveness of the treatment method. The following is combined with the attached Figures 1 to 19 Table 1 further illustrates the process of the present invention. To lay a foundation for broadening the wide application of PPTA reinforced thermoplastic resin-based multifunctional composite materials, the process specifically includes the following steps:
[0065] 1. Principle of Microscopic Co-grafting
[0066] Figure 1 This is a diagram of the co-grafting process of three-phase materials. After modification, the three materials are coupled into a whole through KH560. The surface of PPTA is fully infiltrated with CaCl2 ethanol solution, causing the surface of PPTA to be slightly etched and grooves to appear, while enhancing its surface chemical activity and increasing the attachment points of resin and damping material. CaCl2 has an ionic dipole effect with the amide bond in PPTA, and the -NH- in the amide group is exposed to the hydrogen bond through complexation reaction, thereby increasing its reactivity with the epoxy group in KH560; PC is hydrolyzed with HCl solution to introduce carboxyl groups, which can react with the epoxy group in KH560; VSI is connected to KH560 through Si-O bonds through hydrolysis.
[0067] KH560 builds molecular bridges between materials. The specific connection methods are as follows: Figure 2 As shown, the epoxy group at the tail end of KH560 is ring-opened to react with the carboxyl group in PC to form a chemical bond, and the siloxane at the head end is hydrolyzed to form silanol, which is dehydrated and condensed with the silanol in VSI to form a Si-O-Si connection; Figure 3 The two epoxy groups of KH560 react with the carboxyl group in PC and the secondary amine in PPTA to connect together, while the siloxane at the other end is hydrolyzed to form silanol groups, which are dehydrated and condensed to form a siloxane bond. Figure 4The silane at one end of KH560 forms a chemical bond with VSI after hydrolysis, and the epoxy group at the other end reacts with the secondary amine of PPTA to form a chemical bond, so that the entire structure is connected into a whole through a co-grafting process.
[0068] 2. Composite material modification and preparation process
[0069] 1) Material modification process
[0070] (1) A layer of dichloromethane solution is brushed on the surface of a clean and dry PC sheet to slightly dissolve the PC surface, and then fully soaked in a 1 mol / L hydrochloric acid solution, and placed in a beaker and sealed. The sealed beaker is placed in a high-low temperature alternating wet heat environment box with a working temperature of 60° C. for hydrolysis treatment for 2 hours to obtain a surface carboxylated polycarbonate;
[0071] (2) 10 to 15 cubic centimeters of methyl vinyl silicone rubber (VSI) were cut into granules of 3×3×3 cubic millimeters and placed in a beaker. Dichloromethane solvent was added to the beaker at a mass ratio of 4:1 to dissolve the granular VSI into liquid, and the granules were sealed and stored for later use;
[0072] (3) Cut the PPTA woven cloth into 7 pieces of 160mm×160mm in size, put them into SCQ-1020B ultrasonic cleaning machine for ultrasonic cleaning for 20 minutes, and take them out for high-temperature drying; prepare a CaCl2 ethanol solution with a mass fraction of 10%, put the clean and dry PPTA into the prepared solution, and place it in a high-low temperature alternating wet heat environment box for 2 hours at a constant temperature of 60°C; take out the treated PPTA sample, clean the PPTA with deionized water and dry it, then prepare a KH560 ethanol solution with a mass fraction of 7% and add 5ml of deionized water to promote hydrolysis, and evenly brush it on the surface of the PPTA sample;
[0073] 2) Preparation of composite materials
[0074] VSI liquid was brushed onto the surface of one of the treated PPTA sheets and dried to make a 0.2 mm thick damping film. A layer of the prepared KH560 solution was brushed onto the damping film. According to the designed layering sequence, the PC sheets and PPTA samples were alternately stacked and laid, and the damping film was clamped in the center (such as Fig.19 The laminated composite preform is placed in a press molding die with a unit area working pressure of 1 MPa. Figure 5 As shown in the co-grafting process curve, after hot-pressing co-grafting molding, pressurization is then applied to eliminate residual stress to obtain a PPTA / PC laminate with embedded damping film.
[0075] 3. Confirmatory testing and characterization of composite material samples prepared according to the above method
[0076] The representations here include:
[0077] 1) Fourier transform infrared spectrometer (FTIR) was used to analyze the changes in surface functional groups before and after PPTA modification, PC modification, and VSI modification, so as to determine whether KH560 reacts chemically with each material through the co-grafting process to form chemical bonds and form molecular bridge connections.
[0078] 2) Use field emission scanning electron microscopy to observe the surface morphology of the material at each processing stage and analyze the changes in the microstructure.
[0079] 3) Use INCAX-MAX 50 X-ray energy spectrometer to conduct qualitative analysis on the changes in element types in PPTA micro-areas.
[0080] 4) The H extraction force test and interlaminar shear strength test were carried out on PPTA before and after coating with KH560 to verify the effect of grafting KH560 on improving the bonding performance between rubber and fiber. The equipment used was GT-TCS-2000 electronic universal tensile testing machine.
[0081] Observe the chemical bond changes of each material at different processing stages through FTIR spectra
[0082] As shown in Figure 6(a), the infrared spectrum of untreated PPTA is 3262 cm -1 The NH stretching vibration peak in the secondary amide is 1631 cm -1 The infrared characteristic peak of secondary amide I is at 1515 cm -1 The infrared characteristic peak of secondary amide II is 1297 cm -1 The infrared characteristic peak of secondary amide III is shown at the bottom.
[0083] Figure 6(b) is the infrared spectrum of PPTA coated with KH560. Compared with Figure 6(a), the three characteristic bands of the secondary amide group disappear. This is due to the reaction between the epoxy group in KH560 and the secondary amide group in PPTA; 2800-3000cm -1 The two peaks at 913 cm are the characteristic infrared peaks of methylene in KH560. -1 The infrared absorption peak of epoxy group is 1078cm -1 The antisymmetric stretching vibration absorption peak of Si-O-Si at 800 cm -1 The left and right Si-O-Si symmetric stretching vibration infrared absorption peaks are the characteristic peaks of the introduced KH560; 1640m -1The peak at is caused by the stretching vibration of C=O in the tertiary amide generated by the reaction of the secondary amide and the epoxy group. The changes in the above infrared characteristic peaks prove that the epoxy group in KH560 reacts with the secondary amide in PPTA, the secondary amine is dehydrogenated to become a tertiary amine, and the epoxy group is ring-opened and connected to the tertiary amine.
[0084] Figure 6(c) shows the infrared spectra of PC hydrolysis and PC grafted with KH560. It can be seen from the figure that carboxyl groups are introduced into PC after hydrolysis, with the 2700-3500cm -1 The broad and scattered peaks are caused by the stretching vibration of OH in the carboxyl group. After grafting KH560, the epoxy group in KH560 reacts with the carboxyl group in PC, resulting in the disappearance of the infrared characteristic peak of the carboxyl group and the introduction of the infrared characteristic peaks of the methylene, epoxy and silicon-oxygen bonds of KH560.
[0085] Figure 6(d) is the infrared spectrum of VSI, and Figure 6(e) is the infrared spectrum of VSI grafted with KH560. By comparing the two figures, it can be found that the infrared characteristic peak of KH560 appears in VSI, proving that KH560 is grafted on VSI. By observing the infrared spectra of each material grafted with KH560 and analyzing the changes in chemical groups and chemical bonds, it is proved that KH560 can react chemically with each material to form a chemical bond connection.
[0086] Scanning electron microscope SEM micrograph
[0087] The microstructure SEM images of resin and fiber at each processing stage are shown in Figure 2. Figures 7 to 11 As shown. Figure 7 It can be seen that the surface of untreated PPTA is smooth and neat, compared with Figure 8 The surface of PPTA in the solution becomes rough after being treated with CaCl2, with a small amount of grooves and chelating points for mechanical engagement of resin and rubber. Fig. 9 The microscopic morphology of the PPTA surface after grafting with KH560 shows that the surface of PPTA becomes rougher after grafting with KH560, and a large number of chelating points appear on the fiber surface after KH560 is polymerized. Fig.10 and Fig.11 In comparison, the surface of PC grafted with KH560 becomes rough, which is caused by the deposition of KH560 on the PC surface.
[0088] EDS Spectroscopy
[0089] The test locations are indicated in the SEM images ( Figure 12 to Figure 14 ), the experimental results are: Fig.15 (Score Figure 1 ) shows the EDS spectrum of the untreated PPTA surface. Fig.16 (Score Figure 2) is the EDS spectrum of KH560-PPTA interface. By comparing the two, it can be found that there are a lot of Si elements on the surface of PPTA introduced with KH560, which is the result of KH560 deposition on the PPTA surface; Fig.17 (Score Figure 3 ) is the EDS spectrum of KH560-PPTA-VSI interface. Due to the application of VSI rubber, the Si content on the skin surface is further increased.
[0090] H extraction test
[0091] H test extraction process is as follows Fig.18 As shown, the specimen diagram a represents the VSI vulcanized rubber strip, and b represents the PPTA fiber bundle. The fiber bundles before and after the KH560 coating are respectively embedded in the rubber strip, and then placed in the mold. The mold is placed in a flat vulcanizer and vulcanized at 240°C for 20 minutes. After the rubber strip is taken out and left to stand at room temperature for 48 hours to eliminate the residual stress, a tensile test is performed using an electronic tensile testing machine.
[0092] Interlaminar shear strength test
[0093] Use Fig.19 The specimen shown in the figure tests the interlayer bonding strength. Two cuts are made on the front and back sides of the specimen so that the PPTA layer is broken and the middle rubber layer is not affected, ensuring that only the rubber layer has shear force during the tensile test. The composite specimen size is 150mm*25mm. An electronic universal tensile testing machine (model: GT-TCS-2000) is used to perform tensile tests on the composite specimens. At least 10 samples are tested in each group. Set the tensile test to measure the maximum tensile force F that the specimen can withstand. max , so as to analyze its interlayer bonding performance, and the test results are shown in Table 1. Interlayer shear stress τ j for:
[0094]
[0095] In which, formula (1) τ j is the interlaminar shear stress of the specimen, in Pa; F max is the maximum tensile force value, in N; S j is the shear surface area, in m 2 .
[0096] The prepared test specimens were divided into two groups: before modification and after modification. Five specimens were tested in each group, 1-5 were specimens before modification, and 6-10 were specimens after modification. The test results are shown in Table 1.
[0097] Table 1 shows the test results of interlaminar shear properties and H extraction properties of PPTA reinforced carboxyl PC damping film VSI sandwich thermoplastic composites.
[0098] From the data in Table 1, it can be seen that the H extraction force of the specimen grafted with KH560 increased by 137%, the interlaminar shear stress increased by 74%, and the interface bonding performance between the composite materials was significantly improved.
[0099] Table 1
[0100] serial number Shear stress / MPa H Extraction force / N 1 4.73 21.56 2 4.51 19.89 3 4.45 19.44 4 4.15 23.25 5 5.01 21.75 6 7.46 51.17 7 7.23 52.53 8 7.18 47.48 9 6.79 49.46 10 7.22 49.83
[0101] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.
Claims
1. A method for interfacial modification of PPTA-reinforced carboxyl PC damping film sandwiched thermoplastic composite material, characterized in that: The following steps are involved: 1) Carboxylating the surface of the polycarbonate sheet and sealing it for future use; 2) Cut the methyl vinyl silicone rubber into particles and put them into a beaker. Add dichloromethane solvent to the beaker in a mass ratio of 4:1 to dissolve the methyl vinyl silicone rubber particles into liquid. Seal and store for later use. 3) Cut the para-aramid fiber woven fabric into multiple samples, put them into a cleaning machine for cleaning, and take them out for drying; 4) preparing a CaCl2 ethanol solution, placing the para-aramid fiber sample prepared in step 2) into the prepared CaCl2 ethanol solution, and placing it in a high-low temperature alternating wet heat environment box for constant temperature treatment; 5) taking out the para-aramid fiber sample treated in step 4), washing the para-aramid fiber sample with deionized water and drying it, then preparing a KH560 ethanol solution and dropping deionized water to promote hydrolysis, and evenly brushing it on the surface of the para-aramid fiber sample; 6) brushing the methyl vinyl silicone rubber liquid prepared in step 2) onto the surface of one of the para-aramid fiber samples prepared in step 5) and drying it to make a damping film, and brushing a layer of the prepared KH560 ethanol solution on the damping film; 7) The polycarbonate sheets treated in step 1) and the para-aramid fiber samples treated in step 5 are alternately stacked and laid to form a matrix phase and a reinforcement phase combination, and the damping film prepared in step 6) is then sandwiched into the center position of the aforementioned matrix phase and reinforcement phase combination as a functional phase to form a composite material preform, and the laminated composite material preform is placed in a press molding die, and after hot-pressing and co-grafting molding according to the co-grafting process curve, pressurization is applied to eliminate residual stress to obtain a para-aramid fiber / polycarbonate laminated workpiece embedded with a damping film.
2. The method for interfacial modification of PPTA-enhanced carboxyl PC damping film-embedded thermoplastic composite material as claimed in claim 1, characterized in that: The carboxylation treatment in step 1) uses a dichloromethane solution and a 1 mol / L hydrochloric acid solution.
3. The method for interfacial modification of PPTA-enhanced carboxyl PC damping film-embedded thermoplastic composite material as claimed in claim 1, characterized in that: The cleaning time in step 3) is 20 minutes.
4. The method for interfacial modification of PPTA-enhanced carboxyl PC damping film-embedded thermoplastic composite material according to claim 1, characterized in that: The mass fraction of the CaCl2 ethanol solution in step 4) is 10%.
5. The method for interfacial modification of PPTA-enhanced carboxyl PC damping film-embedded thermoplastic composite material according to claim 1, characterized in that: The temperature in the high-low temperature alternating damp heat environment box in step 4) is 60° C. and the treatment time is 2 hours.
6. The method for interfacial modification of PPTA-enhanced carboxyl PC damping film-embedded thermoplastic composite material according to claim 1, characterized in that: The mass fraction of the KH560 ethanol solution in step 5) is 7%, and the volume of deionized water is 5 ml.
7. The method for interfacial modification of PPTA-enhanced carboxyl PC damping film-embedded thermoplastic composite material as claimed in claim 1, characterized in that: The thickness of the damping film in step 6) is 0.1-0.5 mm.
8. The method for interfacial modification of PPTA-enhanced carboxyl PC damping film-embedded thermoplastic composite material as claimed in claim 1, characterized in that: The mass fraction of the KH560 ethanol solution in step 6) is 7%.
9. The method for interfacial modification of PPTA-enhanced carboxyl PC damping film-embedded thermoplastic composite material as claimed in claim 1, characterized in that: In the step 7), the working pressure per unit area of the press molding die is 1 MPa.
Citation Information
Patent Citations
Method for increasing surface roughness of aramid fiber
CN109610171A
Method for enhancing interface adhesive force of rubber composite material through aramid nanofiber surface modification
CN115449097A